2022
DOI: 10.1029/2021sw002850
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Disturbances Observed From a Single GPS Station in Hong Kong During the Passage of Super Typhoon Hato in 2017

Abstract: The powerful convection in the lower atmosphere, for example, tropical cyclones (TCs), has a high probability of causing ionospheric disturbances. We observed evident ionospheric disturbances during the passage of Super Typhoon Hato in 2017 by analyzing the highest elevation vertical total electron content (HeVTEC) time series, that is, the VTEC from the Global Positioning System (GPS) satellite with the highest elevation at each epoch, retrieved from a single GPS station in Hong Kong. The results demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…More recently, Yu et al. (2022) studied evident TEC fluctuations ranging from 33.5 TECU to the peak value of 62.0 TECU during the passage of Super Typhoon Hato in 2017 based on a single GPS station in Hong Kong.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Yu et al. (2022) studied evident TEC fluctuations ranging from 33.5 TECU to the peak value of 62.0 TECU during the passage of Super Typhoon Hato in 2017 based on a single GPS station in Hong Kong.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ratovsky et al (2022) attributed the source of same extreme ionospheric events to geomagnetic activity and sudden stratospheric warming (SSW). Also, Yu et al (2022) reported an increase to about 60TECu during the passage of Typhoon Hato. Other weather events have also been reported to have such similar increment (Suparta & Yusop, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…On the day of landfall, the ionospheric TEC over Hong Kong region experienced great enhancement, the peak value 62.0 TECu occurred on the landfall day, approximately twice as high as that of non-typhoon impacted days, which was considered to be related to Hato (Yu et al, 2022). It should be noted that Yu et al (2022) relies solely on highelevation angle data from stations in Hong Kong region, which may result in limited spatial coverage and incomplete information about the ionospheric response. It is noteworthy that Typhoon Hato made landfall while a weak magnetic storm was occurring.…”
Section: Space Weathermentioning
confidence: 99%
“…Studies on ionospheric variations during typhoon passage in East Asian, Australian, and North American regions shown that these regions sometimes experience positive or negative deviations in TEC during typhoon events (W. Li et al, 2017Li et al, , 2018Mao et al, 2010;Yu et al, 2022). It should be noted that due to the complex variability of the ionosphere and limitations in data processing methods, some results of these studies may also carry some uncertainty in determining the precise extent of deviation caused by the impact of typhoons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation